The electric field gradient asymmetry parameter in InSe - Kovalyuk, Z.D.; Khandozhko, A.G.; Lastivka, G.I.; Samila, A.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The complex NQR spectra of ¹¹⁵In caused by presence of structural defects called polytypes are observed in a monocrystalline InSe sample. Multiple ratio of average frequencies of NQR spectra that correspond to four resonance transitions of quadrupole nuclii with spins I = 9/2 testifies to existence of axial symmetry of the electric field gradient in In nucleus positions inside the InSe crystal structure. The latter is confirmed by the dependence of the NQR spectrum amplitude on the angle between the main crystal axis c and vector of high-frequency field H₁. However, presence of a residual intensity in the spectra at c || Н₁ can indicate the existence of crystal blocks in bulk of the sample with weak angular misorientation.